Algal chloroplast produced camelid VHH antitoxins are capable of neutralizing botulinum neurotoxin. Issue 1 (17th September 2014) - Barrera, Daniel J.; Rosenberg, Julian N.; Chiu, Joanna G.; Chang, Yung‐Nien; Debatis, Michelle; Ngoi, Soo‐Mun; Chang, John T.; Shoemaker, Charles B.; Oyler, George A.; Mayfield, Stephen P.
Summary We have produced three antitoxins consisting of the variable domains of camelid heavy chain‐only antibodies (VHH) by expressing the genes in the chloroplast of green algae. These antitoxins accumulate as soluble proteins capable of binding and neutralizing botulinum neurotoxin. Furthermore, they accumulate at up to 5% total soluble protein, sufficient expression to easily produce these antitoxins at scale from algae. The genes for the three different antitoxins were transformed into Chlamydomonas reinhardtii chloroplasts and their products purified from algae lysates and assayed for in vitro biological activity using toxin protection assays. The produced antibody domains bind to botulinum neurotoxin serotype A (BoNT/A) with similar affinities as camelid antibodies produced in Escherichia coli, and they are similarly able to protect primary rat neurons from intoxication by BoNT/A. Furthermore, the camelid antibodies were produced in algae without the use of solubilization tags commonly employed in E. coli. These camelid antibody domains are potent antigen‐binding proteins and the heterodimer fusion protein containing two VHH domains was capable of neutralizing BoNT/A at near equimolar concentrations with the toxin. Intact antibody domains were detected in the gastrointestinal (GI) tract of mice treated orally with antitoxin‐producing microalgae. These findings support the use of orally delivered antitoxins produced in green algae as a novel treatment for botulism.